Respuesta :

Answer:

x = [tex]-\frac{24}{7}[/tex]

Step-by-step explanation:

x - 8y = -16

6x + 8y = -8

= 7x = -24

Divide both sides by 7;

x = [tex]-\frac{24}{7}[/tex]

Answer:

Step 1: Get rid of y and solve for x by using elimination.

[tex]-8y = -16\\6x + 8y = -8\\\\6x = 24\\\\x = 4[/tex]

Step 2: Plug what we found for x in the SECOND equation, then solve for y.

[tex]6(4) + 8y = -8\\\\24 + 8y = -8\\\\8y = -32\\\\y = -4[/tex]

Now, we can put both numbers together for our solution.

(4, -4)